2018
DOI: 10.3892/ol.2018.7795
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin domain receptor 1: New star in cancer-targeted therapy and its complex role in breast carcinoma (Review)

Abstract: Abstract. Discoidin domain receptor 1 (DDR1) is a receptor tyrosine kinase activated by various types of collagens that performs a critical role in cell attachment, migration, survival and proliferation. The functions of DDR1 in various types of tumor have been studied extensively. However, in breast carcinoma, the roles of collagen-evoked DDR1 remain ill defined. Although a number of studies have reported that DDR1 promotes apoptosis and inhibits migration in breast carcinoma, it has also been reported to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 88 publications
0
30
0
Order By: Relevance
“…DDR1 is a unique member of RTK family and was first identified during a search for tyrosine kinase proteins expressed in human breast carcinoma (Jing et al ., ; Johnson et al ., ). It has been reported that DDR1 is significantly overexpressed in several human tumors.…”
Section: Discussionmentioning
confidence: 97%
“…DDR1 is a unique member of RTK family and was first identified during a search for tyrosine kinase proteins expressed in human breast carcinoma (Jing et al ., ; Johnson et al ., ). It has been reported that DDR1 is significantly overexpressed in several human tumors.…”
Section: Discussionmentioning
confidence: 97%
“…These results imply that the OSCC cells might have been addicted to overexpressed DDR1 for their survival. In the same vein, targeting DDR1 alone or in combination with other chemotherapies have been suggested in several neoplasms, including metastatic colorectal cancer, K-RAS driven lung adenocarcinoma, and breast carcinoma [14,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that DDRs are major players in cancer progression in multiple cancer types (Jing, Song, & Zheng, 2018;Rammal et al, 2016;Valiathan et al, 2012). However, there is a paucity of information on the expression and roles of DDRs in melanoma (Cario, 2018).…”
Section: Discussionmentioning
confidence: 99%